A reclama????o constitucional como instrumento de atualiza????o da jurisprud??ncia do Supremo Tribunal Federal - Viana, T??lio Machado (2015)
This work aims to discuss, from the analysis of the Rcl 4374/PE, the use of the constitutional complaint as a instrument processual able to promote the update of the jurisprudence of the Supreme Court, which are firmed under abstract judicial review of the standards. It assumes that the Court???s decisions remain open to a constant process of reinterpretation, by itself, and the constitutional complaint can be the locus for assessment of those changes. It understands that the Constitution of a State, under the guise of being stable, can???t stifle in a way that fails to meet the interests of its people, leading to an institutional breakdown. At the same time, it cannot be subject to a process of deformation through constant changes in its text, destabilizing the legal relations. The question which arises, therefore, is the idea that the Constitution must be interpreted in a temporal context in which required the solution of a given case. Similarly, the judicial decisions which care about the relationship between the standards, whereas continuing legal relationship, aren???t precluded from being modified when there is a material change of context. So, when considering the occurrence of substantial changes in the factual relationships or general legal concept, this reinterpretative process can lead to an evolution in the jurisprudence set in an abstract control of the standards and result in an unconstitutionality, when it was considered constitutional before. Thus, it is proposed the understanding that the legal standards suffer a permanent process of updating of their meaning, which is why the study of the phenomenon of constitutional mutation and interpretation arises as being of great relevance for this update take place. The constitutional mutation is recognized as one of the most important contemporary discussions in Law, by providing a radical change in the interpretation of the Constitution, allowing its renewal, at the light of the social evolution, and offering meanings in line with the current reality